Analisis Resepsi Khalayak terhadap Pola Asuh Anak dalam Konten TikTok @rensia_sanvira - Diah Ayu Septiana; Riski Apriliani (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study analyzes audience interpretation of parenting messages contained in TikTok content by @rensia_sanvira. It focuses on audience reception, emphasizing that the audience is an essential component of communication who actively receives and interprets messages delivered by the media, including the TikTok content of @rensia_sanvira. The background of this research stems from the growing public concern over inappropriate parenting practices and the increasing use of social media as a platform for parenting education. The aim of this study is to understand how parent viewers interpret parenting messages in the content shared by @rensia_sanvira on TikTok. Data were collected through in-depth interviews with five individuals who are active followers of the TikTok account @rensia_sanvira. This research employed a reception analysis method based on Stuart Hall’s encoding-decoding theory, using a descriptive qualitative approach. Informants were selected using purposive sampling, involving specific criteria for inclusion. The results show that two informants occupied a dominant-hegemonic position, three held a negotiated position, and none were found in the oppositional position. This study concludes that the TikTok content of @rensia_sanvira effectively delivers parenting messages that are empathetic, educational, and highly relevant to the social realities of parents.